Urinary NephroCheck test, as a marker of subclinical postoperative AKI, correlates with long-term GFR decline in patients undergoing partial nephrectomy: a prospective bicentric observational study - Allinovi, Marco; Walach, Margarete; Casiraghi, Micaela Anna; Weidenbusch, Marc; Innocenti, Samantha; Tofani, Lorenzo; Paparella, Laura; Fanelli, Alessandra; Villa, Gianluca; Nuhn, Philipp (BMC nephrology, 2025)
Nephron-sparing surgery (NSS) represents the preferred technique to treat localized renal lesions, not being exempted from the risk of postoperative acute kidney injury (AKI) to happen, though. Patients experiencing postoperative AKI, either clinical or subclinical, are more susceptible to develop chronic kidney disease. Patients scheduled for NSS in localized renal cell carcinoma were recruited. Patients were grouped according to postoperative AKI development and postoperative NephroCheck value: group 1 (normal), no AKI and no increased biomarker; group 2 (subclinical AKI), no AKI but increased NephroCheck (> 0.3 at 4 h postoperatively); group 3, AKI and no increased NephroCheck; group 4 (clinical AKI), AKI and increased NephroCheck. Samples were collected pre- and post-operatively; renal function was re-assessed up to 24 months. Among 131 patients included, 42% developed clinical AKI. Based on NephroCheck® and clinical AKI criteria, patients could be divided in four groups with significantly different eGFR at 24 months (p = 0.0003). Multivariate analysis confirmed clinical AKI as an independent predictor of eGFR decline at 24 months (p < 0.0003). In subclinical AKI’s subgroup [20/131 (15%)], characterized by urinary NephroCheck® >0.3 and serum creatinine increase < 0.3 mg/dL, NephroCheck® appeared as an independent predictor of severe eGFR decline at 24 months (OR 3.76, p = 0.02); in this subgroup, eGFR decline resulted significantly more severe compared to eGFR decline in patients with neither serum creatinine nor tubular damage markers’ elevation. In patients undergoing NSS, the most reliable predictor of long-term eGFR decline is represented by the occurrence of postoperative clinical AKI. In this setting, NephroCheck® appeared able to identify ‘subclinical AKI’ and consequently patients at increased risk of 24-month-eGFR decline.
Gesehen am 26.08.2025